2021
DOI: 10.1177/07334648211028393
|View full text |Cite
|
Sign up to set email alerts
|

“There Is Something Very Personal About Seeing Someone’s Face”: Provider Perceptions of Video Visits in Home-Based Primary Care During COVID-19

Abstract: The rapid deployment of video visits during COVID-19 may have posed unique challenges for home-based primary care (HBPC) practices due to their hands-on model of care and older adult population. This qualitative study examined provider perceptions of video visits during the first wave of the COVID-19 crisis in New York City (NYC) through interviews with HBPC clinical/medical directors, program managers, nurse practitioners/nurse managers, and social work managers ( n = 13) at six NYC-area practices. Providers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
13

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 27 publications
3
42
0
13
Order By: Relevance
“…During the COVID-19 pandemic, EFCs were more important than ever ( Tupper et al, 2020 ) given the consequences of the visitor restrictions including decreased resident well-being and quality of life ( O’Caoimh et al, 2020 ; Stall et al, 2020 ), long periods of social isolation ( Chu et al, 2020 ; Chu, Wang et al, 2021 ), and diminished informal care provided by families ( Avidor & Ayalon, 2021 ). Virtual visits for older adults have been utilized to facilitate virtual care during COVID-19 ( Franzosa et al, 2021 ) and as a means to connect residents to family and friends ( Sacco et al, 2020 ). Despite the use of technology-based visits, there are barriers related to technology use among older adults in LTCHs, which have made its application challenging ( Chu, Ronquillo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, EFCs were more important than ever ( Tupper et al, 2020 ) given the consequences of the visitor restrictions including decreased resident well-being and quality of life ( O’Caoimh et al, 2020 ; Stall et al, 2020 ), long periods of social isolation ( Chu et al, 2020 ; Chu, Wang et al, 2021 ), and diminished informal care provided by families ( Avidor & Ayalon, 2021 ). Virtual visits for older adults have been utilized to facilitate virtual care during COVID-19 ( Franzosa et al, 2021 ) and as a means to connect residents to family and friends ( Sacco et al, 2020 ). Despite the use of technology-based visits, there are barriers related to technology use among older adults in LTCHs, which have made its application challenging ( Chu, Ronquillo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the use of technology-based visits, there are barriers related to technology use among older adults in LTCHs, which have made its application challenging ( Chu, Ronquillo et al, 2021 ). For instance, the lack of affordable devices and internet services, older adults’ lack of confidence and digital literacy to navigate the use of the technology, and the technologies are not designed with older people in mind may deter their use ( AGE-WELL National Innovation Hub, 2018 ; Barnard et al, 2013 ; Chu, Nyrup et al, 2021 , Damodaran et al, 2014 ; Franzosa et al, 2021 ; Martins Van Jaarsveld, 2020 ; Vaportzis et al, 2017 ; Vassli & Farshchian, 2018 ). Another challenge is the poor digital infrastructure of LTCHs to support technology use, such as limited internet connections that are often in outdated physical buildings and a lack of technology support for staff ( Chu, Ronquillo et al, 2021 ; Moyle et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…While all CR team members indicated a preference for doing CR in person, in line with other healthcare providers’ preference that provision of this type of remote care be temporary ( Franzosa et al, 2021 ), five out of eight were willing to do TBCR in the future, particularly for addressing the non-exercise-related components of CR. Despite this preference, all participants recognized that TBCR was preferable to no program at all.…”
Section: Discussionmentioning
confidence: 91%
“…The present study found that older adults have substantially increased the utilization of telehealth during the COVID-19 outbreak, and that learning a new technology is associated with the adoption of telehealth. Although emerging evidence suggests that learning a new technology is related to older adults’ adoption of telehealth during the COVID-19 outbreak ( Franzosa et al, 2021 ; Hawley et al, 2020 ), these findings have been based on community samples and qualitative designs. By using data from a national survey, the present study findings complement previous evidence by examining technology learning and the adoption of telehealth during the outbreak at a population level.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from a pilot program on rapid integration of home telehealth suggest that short-term technology learning may facilitate immediate adoption of telehealth ( Hawley et al, 2020 ). Additionally, qualitative evidence shows that the ability to quickly learn a new technology is crucial to older adults’ adaptation to telehealth during the outbreak ( Franzosa et al, 2021 ). However, population level evidence is scant on learning a new technology and quick adoption of telehealth among older adults during the outbreak.…”
Section: Introductionmentioning
confidence: 99%